STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA DAN MOTIVASI KERJA GURU DI SEKOLAH DASAR - Euis Fidyana; B Herawan Hayadi; Minkhaermidah Minkhaermidah; Anton Setiabudi; Siti Mutmainah (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Leadership is a person's ability to influence, direct, and mobilize other people or groups to work together to achieve common goals effectively and efficiently. This study aims to analyze the leadership strategy of school principals in improving teachers' performance and work motivation in elementary schools. The problems found in the field show that teachers' performance and work motivation are not optimal, which is characterized by a lack of discipline in learning administration, low innovation in the learning process, and lack of maximum professional responsibility for teachers. This